Capsaicin and capsiate could be appropriate agents for treatment of obesity: A meta-analysis of human studies. Issue 9 (13th June 2018) - Zsiborás, Csaba; Mátics, Róbert; Hegyi, Péter; Balaskó, Márta; Pétervári, Erika; Szabó, Imre; Sarlós, Patrícia; Mikó, Alexandra; Tenk, Judit; Rostás, Ildikó; Pécsi, Dániel; Garami, András; et al.
ABSTRACT: Consumption of capsaicin or its nonpungent analogues, capsinoids has been reported to affect energy expenditure and fat oxidation, although available data are still controversial. The aim of the present study was to conduct a meta-analysis regarding the effects of these substances on energy expenditure and respiratory quotient, with special emphasis on the role of body mass index (BMI) of the participants. Medical databases were systematically searched for papers. Of the 627 trials identified, 9 provided results suitable to be included in analysis. Data analysis showed that after ingestion of capsaicin or capsinoids the energy expenditure increased (245 kJ/day, 58.56 kcal/day, p = 0.030) and the respiratory quotient decreased (by 0.216; p = 0.031) indicating a rise in fat oxidation. Studies with mean BMI of the participants below 25 kg/m 2 failed to report any effect of capsaicin or capsinoids on the energy expenditure ( p = 0.718) or on the respiratory quotient ( p = 0.444), but studies with mean BMI exceeding 25 kg/m 2 demonstrated an increase in energy expenditure (292 kJ/day, 69.79 kcal/day, p = 0.023) and a marked decrease in respiratory quotient (−0.257, p = 0.036). Our data clearly suggest that capsaicin or capsiate could be a new therapeutic approach in obesity promoting a negative energy balance and increased fat oxidation.